Experimental and theoretical study on cable-supporting system. (June 2020) - Fei, Han; Danhui, Dan; Yiqing, Zou; Huan, Lei
Highlights: An exact method for dynamic analysis of suspension type cable systems is proposed. Consider multiple effects such as flexural stiffness, sag, and elastic supports simultaneously. A full-scale cable test is used to strictly verify the accuracy of the method. Abstract: Suspension type cable system is an important type of cable bearing system, its dynamic problems have always been the key to the structural design, health monitoring, and vibration control. In view of this, an exact dynamic analysis method for suspension type cables is proposed by the author. The dynamic characteristic of the suspension cable system is studied by a full-scale cable test. By comparing with experimental results and finite element solutions, the accuracy and universality of the proposed method are verified. The results show that the calculation result agrees well with the measured results, and the maximum relative error of each condition is basically no more than 2%. Through parameter identification, the bending stiffness, cable force, and the installation position of the weights are identified and corrected, and the calculation errors after parameter identification are controlled within 1%, which significantly improves the calculation accuracy and further verifies the accuracy of the proposed method.